Sri Lanka : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Use of Fund Resources-Request for an Extended Arrangement-Staff Report; Staff Statement; News Brief on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper examines Sri Lanka's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and a Request for an Extended Arrangement. In line with the Poverty Reduction Strategy Paper (PRSP) and building on the progress made under the Stand-By Arrangement (SBA), the PRGF-Enhanced Fund Facility (EFF)-supported program aims to accelerate economic growth and reduce poverty. The IMF staff recommends extension to the obligations schedule of SBA repurchase expectations arising during July 2003-June 2004.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet